2011
DOI: 10.1021/jp205874k
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Micelles as Templates for the Preparation of Silica Nanodisks

Abstract: We have reported earlier that silica nanodisks are formed by the reverse micelle solÀgel (RMSG) method, from ternary Aerosol OT (AOT)/nheptane/water mixtures. These nanodisks are formed from the ternary mixtures with higher water contents and containing a significant concentration of FeCl 3 . Such mixtures undergo a phase separation. The present work seeks to identify the origin of these nanodisks. They are found to be produced from the lower, water-rich layer and not from the upper, oil-rich layer or from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…15,22,26 The mixture is then shaken thoroughly to aid dissolution and subsequently left undisturbed for 1-2 days so as to attain equilibrium and complete phase separation with a clear water rich layer. Ternary mixtures of w 0 , a measure of molar ratio of water to AOT, 300 and 150 are prepared in a separating funnel by mixing required amount of AOT in nheptane and water containing C153.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,22,26 The mixture is then shaken thoroughly to aid dissolution and subsequently left undisturbed for 1-2 days so as to attain equilibrium and complete phase separation with a clear water rich layer. Ternary mixtures of w 0 , a measure of molar ratio of water to AOT, 300 and 150 are prepared in a separating funnel by mixing required amount of AOT in nheptane and water containing C153.…”
Section: Methodsmentioning
confidence: 99%
“…In water, however, AOT molecules aggregate to form two dimensional flat lamellar structures. 15 Even though the fundamental structural aspects of these lamellar assemblies are similar to regular micelles, changes in degree of hydration and connectivity of water pools have been observed due to loss of dimensionality. 14 These lamellar structures are anisotropic and therefore, exhibit birefringence, unlike regular micelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution was then mixed vigorously for 1 min to obtain a transparent micellar solution. The desired water content was defined as the R value, which indicates the molar ratio of water to surfactant ([H 2 O]/[surfactant]) (Banerjee, Ghosh, & Datta, 2011), and the glycerol content was defined as the G value, which indicates the molar ratio of glycerol to surfactant ([glycerol]/[surfactant]) (Park et al, 2010). The R and G values were calibrated by considering the amount of water inherently present in the isooctane, glycerol, and AOT.…”
Section: Preparation Of Reverse Micellesmentioning
confidence: 99%
“…In the present work, we have adopted a similar approach as Weisner and co-workers, but have used anisotropic silica nanodisks prepared using lamellar micelles as templates. [20][21][22] These nanodisks are likely to have important applications in drug delivery and sensing in biological media, as Mitragotri and co-workers have shown that anisotropic structures are less prone to phagocytosis by macrophages and consequent ejection from the body. 23,24 Further, we have used these core-shell nanoconjugates as a platform to explore the feasibility of pH sensing with the fluorescence lifetimes, in addition to the ratios of intensities.…”
Section: Introductionmentioning
confidence: 99%